Research on the Value, Risks, and Responses of DeepSeek Empowering Vocational Education - Jianan Guo (Journal of Exploration of Vocational Education, 2025)
With the rapid development of artificial intelligence technology, the application of DeepSeek big model in higher vocational education is becoming increasingly widespread, promoting the digital transformation of education. In terms of value, DeepSeek technology empowers teaching management, helps improve teaching levels, empowers learning planning, helps improve student learning efficiency, empowers teaching coaching, helps improve teacher teaching quality, empowers educational resources, and facilitates the integration of different educational resources. Reflecting on current developments, the modernization of higher vocational education in the DeepSeek era is facing threats to personal privacy and data security, risks of moral alienation among students, challenges to traditional authority of teachers, and the potential exacerbation of the digital divide in education. To achieve the leapfrog development of modernization of higher vocational education from "latecomer" to "advanced" with the help of artificial intelligence technologies such as DeepSeek, it is necessary to strengthen the supervision and regulation of the application of DeepSeek technology, implement the fundamental task of moral education to achieve comprehensive human development, cultivate "smart" teachers to demonstrate the unique value of "human teachers", optimize the allocation of digital education resources to promote educational equity, deepen the integration of intelligent technology and higher vocational education, and ensure that DeepSeek technology becomes an important support for promoting high-quality development of higher vocational education and cultivating high-quality technical and skilled talents.